Cattle, canines, and culture: reconstructing human-animal relationships in the Bronze Age Aegean - Murphy, Ciara (2024)
Human-animal study (HAS) is a vast area of research that offers many avenues for exploration. In modern times, dogs and cattle are ubiquitous, whether as pets, working animals in the fields, or sources of food. Each interaction between humans and animals strengthens their relationship. This was also true in the Bronze Age Aegean (BAA), as the wealth of evidence shows that there were numerous types of interactions based on various factors. Defined by the AVMA (American Veterinary Medical Association, 2023), the human-animal bond is a mutually beneficial relationship influenced by behaviours essential to the health and well-being of both parties. The relationship is influenced by both the animal and the human through the animal’s previous experience, the animal’s genetics, the human’s familiarity with the animal, and the human’s knowledge and skills (Hosey, 2008, 105; Raul et al., 2020, 1). An ethological perspective on HAR focuses on the interaction’s frequency, quality, and context to influence the relationship's overall quality (Breuer et al., 2011, 4-5). The relationships are thus based on a history of regular interactions. This thesis will examine evidence from the BAA to reconstruct human-animal relationships (HAR) with dogs and cattle. As this thesis will show, scholars are understandably hesitant to apply modern research on HAR, at the risk of imposing one’s own experiences onto ancient evidence. Through this thesis, I aim to provide support in favour of relying on modern research where applicable, by exploring the similarities between modern and ancient HAR.